Phylogenetic relatedness within Neotropical fern communities increases with soil fertility. Issue 6 (31st March 2015) - Lehtonen, Samuli; Jones, Mirkka M.; Zuquim, Gabriela; Prado, Jefferson; Tuomisto, Hanna
Abstract Aim To examine the relative importance of gradients in soil fertility and rainfall for the phylogenetic structure of Neotropical forest fern communities, and to quantify how much the results are affected by phylogenetic resolution. Location Tropical lowland forests in Brazil (central Amazonia) and Panama (the Panama canal watershed). Methods We inventoried local fern communities at a total of 87 sites to model how their species richness and phylogenetic relatedness varied along gradients in soil fertility and rainfall. We produced a time‐calibrated species‐level molecular phylogeny of ferns, and quantified the phylogenetic relatedness of species within local communities using Faith's phylogenetic diversity (PD) and mean phylogenetic diversity (MPD). Calculations were compared for phylogenies resolved to the species and genus levels. Results (1) We found significant and consistent effects of soil nutrient status on local phylogenetic community structure in both regions. In contrast, phylogenetic structure showed only a weak or no relationship with rainfall. (2) In both regions, MPD declined with increasing soil fertility, which means that fern communities on poor soils consisted, on average, of less closely related lineages than fern communities on rich soils. (3) Different fern genera were over‐represented in different sections of the soil nutrient gradient. (4) Qualitatively similar results were obtained whether phylogenies were resolved to the species or the genus level. Main conclusions Our results highlight the importance of edaphic variation in structuring plant communities over evolutionary time‐scales. Within the tropical forests studied, the effects of soil variation on local phylogenetic community structure seem to outweigh those of climate. Several fern genera show strong edaphic niche conservatism to either poor or rich soils, whereas many other genera have radiated to span a rather broad edaphic range. PD‐based measures are so dominated by deep relationships that genus‐level phylogenies are sufficient to investigate these patterns in tropical fern communities.